A 55-mm Object Inside a 40-mm Orbit. (22nd July 2013) - Floyd, Anne M.; Whipple, Katherine M.; Lim, Lee Hooi; Korn, Bobby S.; Kikkawa, Don O.
ABSTRACT: A 43-year-old man was struck in the left orbit with his board while surfing and sustained a 3-cm laceration above his left eyebrow. The laceration was sutured closed primarily at a local emergency room. When he presented to UCSD oculoplastics for suture removal, he complained of diplopia with upgaze and was found to have hypoglobus on clinical exam. An orbital CT demonstrated a hyperintense linear signal within the orbit. The patient underwent surgical exploration. A 55-mm-length piece of fiberglass from the patient's surfboard was removed from his orbit. This case demonstrates the importance of having a high index of suspicion for retained orbital foreign bodies, regardless of the size of the object inflicting the injury.